MIGRATION PATTERNS OF LEGACY SYSTEMS TO MICROSERVICES BASED ARCHITECTURE - de Carvalho Cintra, Rafael; Instituto Federal de São Paulo (2019)
Microservice is a software architectural style that has been consolidating in application development projects, consisting in a set of small services. In the same direction, there’s a big demand to migrate legacy systems built in monolithic architecture to this new style with the purpose to take advantage of the technologies from distributed systems. This paper aims to list patterns that can be used in projects that target to migrate an application developed using monolithic approach to a new microservices approach. A survey with IT professionals was executed to validate the applicability of these patterns. Finally, analyzing the results, it observes that the migration patterns listed are treated with relevancy by the researched professionals.